Using the 4-D to Design a Public Speaking Handbook for Students at Miftahul Ulum Boarding School - Imroatul Fathonah; Andi Tenrisanna Syam; Amalia Yahya (Universitas Islam Negeri Mataram, Indonesia, 2025)
This study was conducted to design a Public Speaking Handbook for students enrolled at the Miftahul Ulum Islamic school Boarding. The authors employed the R&D (Research and Development) method by adopting the 4-D model. The research instruments were observation, interviews, and surveys. The research participants comprised 29 students, one teacher, and several other lecturers, who were selected using a purposive sampling method. Quantitative data was collected from surveys, while qualitative data was collected from student records and observations. The researchers conducted a needs analysis and a perception survey on the manual among students. The students' perception score was 3.41, which was considered